Нypeгtriploidy as a cause of early embryonic arrest - A. N. Volkov; L. V. Nacheva (Фундаментальная и клиническая медицина)
Chromosomal abnormalities are a leading cause of early embryonic arrest Identification of genetic abnormalities incompatible with embryonic development significantly contributes to the understanding of early embryonic arrest causes and to the development of prevention strategies. Here we describe a case of hypertriploid abortus with 70, XXY,+16 karyotype. This chromosomal abnormality led to the early embryonic arrest at 4 weeks and 5 days of pregnancy.The clinical report emphasizes the necessity for the cytogenetic analysis of abortion material in the patients who underwent a reproductive failure.